Identifikasi Deformasi Permukaan Gempa Bumi Turki 24 Januari 2020 dengan Teknik Interferometric Synthetic Aperture Radar (INSAR) - Panuntun, Hidayat (2020)
Since the earthquake causes deformation in broadscale area, identification of surface deformations due to an earthquake cannot be carried out conventionally using terrestrial surveys. Alternatively, satellite-based observation offers efficient way to map the surface deformation due to an earthquake. The deformation map then can be used as a tool for post-disaster assessment as part of disaster management systems. Here, the 24 January 2020 Turkey earthquake was investigated using Differential Interferometric Synthetic Aperture Radar (InSAR). A pair of InSAR data was formed using two Sentinel-1 Single Look Complex (SLC) images. The surface deformation then was mapped using converted interferograms through filtering, phase unwrapping and geocoding processes. GMTSAR, an open-source UNIX-based code, was used to process all image data. The results showed that surface deformation due to the 2020 Turkey earthquake is well-mapped by InSAR images. In this case, the most heavily affected area due to this earthquake is easily identified. Coseismic deformation signal is clearly imaged up to a radius of ~20 km from the earthquake epicenter. The result shows an uplift pattern in the vicinity of the epicenter area. The Line of Sight (LOS) displacement are observed from -182.9 mm (subsidence) to 340.3 mm (uplift).